The effector T cells of diabetic subjects are resistant to regulation via CD4+FOXP3+ Treg - Schneider, Anya (2008)
Defects in immune regulation have been implicated in the pathogenesis of diabetes in mouse and in man. In vitro assays using autologous regulatory (Treg) and responder (Teff) T cells have shown that suppression is impaired in diabetic subjects(1). In this study we addressed whether the source of this defect is intrinsic to the Treg or Teff compartment of diabetic subjects. We first established that in T1D individuals similar levels of impaired suppression were seen, irrespective of whether natural Treg (nTreg) or adaptive regulatory T cells (aTreg) were present. Then using aTreg we examined the ability of T1D aTreg to suppress Teff of healthy controls, as compared to the ability of control aTreg to suppress Teff of diabetic subjects. Taking this approach we found that the aTregs from T1D subjects function normally in the presence of control Teff, and that the T1D Teff were resistant to suppression in the presence of control aTreg. This escape from regulation was seen with nTreg as well and was not transferred to control Teff co-incubated with T1D Teff. Thus, the “defective regulation” in T1D is predominantly due to the resistance of responding T cells to Treg, and is a characteristic intrinsic to the T1D Teff. This has implications with respect to pathogenic mechanisms which underlie the development of disease and the target of therapies for T1D.